Sclerostin aggravates insulin signaling in skeletal muscle and hepatic steatosis via upregulation of ER stress by mTOR‐mediated inhibition of autophagy under hyperlipidemic conditions. Issue 11 (10th September 2022) - Oh, Heeseung; Park, Seung Yeon; Cho, Wonjun; Abd El‐Aty, A. M.; Hacimuftuoglu, Ahmet; Kwon, Chang Hyuk; Jeong, Ji Hoon; Jung, Tae Woo
Abstract: Recently, sclerostin (SCL), a circulating glycoprotein, was proposed to be a novel myokine involved in developing metabolic disorders. The association between SCL levels and insulin resistance in skeletal muscle, liver, and adipose tissue was studied in individuals with aggravated glucose tolerance. Thus, we hypothesized that elevated circulating SCL might affect skeletal muscle insulin signaling and hepatic lipid metabolism, and aimed to investigate the effects of SCL on skeletal muscle insulin resistance and hepatic steatosis in obesity using in vitro and in vivo experimental models under hyperlipidemic conditions. In the current study, we found elevated SCL messenger RNA expression levels in myocytes in obese patients. In addition to a higher blood level, SCL was expressed at an elevated level in the skeletal muscle of mice fed a high‐fat diet (HFD). Higher SCL release levels and expression were also noticed in palmitate‐treated C2C12 myocytes. SCL suppression by in vivo transfection improves skeletal muscle insulin resistance and hepatic steatosis in HFD‐fed mice. The treatment of C2C12 myocytes with recombinant SCL aggravated insulin signaling. Furthermore, treatment with SCL augmented lipogenic lipid deposition in human primary hepatocytes. Treatment with SCL upregulated mammalian target of rapamycin (mTOR) phosphorylation and suppressed autophagy markers, thereby causing endoplasmic reticulum (ER) stress. 4‐Phenylbutyric acid, a pharmacological ER stress inhibitor, abolished the effects of SCL on insulin signaling in C2C12 myocytes and lipid accumulation in primary hepatocytes. In conclusion, SCL promotes skeletal muscle insulin resistance and hepatic steatosis by upregulating ER stress via the mTOR/autophagy‐mediated pathway. The present study suggests that antagonizing SCL might be a novel therapeutic strategy for simultaneously managing insulin resistance and hepatic steatosis in obesity. Abstract : Sclerostin (SCL) causes impairment of skeletal muscle insulin signaling. SCL enhances hepatic steatosis. SCL causes endoplasmic reticulum stress due to downregulation of autophagy signaling, thereby provoking skeletal muscle insulin resistance and hepatic steatosis.